Novel of chronic phase of Canine Uveodermatologic Syndrome (Vogt-Koyanagi-Harada-like syndrome) - Eroksuz, Yesari; Dubielzig, R. Richard (Ankara Univ Press, 2014)
The aim of the present study is to evaluate morphological findings of chronic uveodermatologic syndrome (UDS) in dogs. Five canine cases which had been diagnosed as chronic form of canine UDS pathologically were re-evaluated for histopathologically and immunohistochemically (CD3 and CD20). The dogs were from different breeds with the mean of 6-year-old (range 3 to 12 years) and enucleated globes were submitted from the different animal hospitals with the history of bilateral uveitis that was uncontrollable with anti-inflammatories, followed by glaucoma and blindness. Microscopically; mild to moderate lymphoplasmacytic uveitis together with histiocytic pigment phagocytosis, melanin containing macrophage infiltration and epithelial depigmentation were the main findings detected. Secondary glaucoma, synechia and iris bombe were also seen. The B lymphocytes were predominantly found in affected parts of the globe including iris, ciliary body, cilliary process and choroid. In conclusion, the chronic phase of canine uveodermatologic syndrome is characterized by mild to moderate lymphoplasmacytic uveitis or panuveitis. Although chronic form has not been reported in earlier canine reports, it is compatible with the chronic form of Vogt-Koyanagi-Harada cases in humans.
Köpeklerin uveodermatolojik sendromunda (Vogt-Koyanagi-Harada benzeri sendrom) kronik dönem lezyonlari{dotless}
Keywords: Chronic phase; dog; histopathology; immunohistochemistry; Uveodermatologic Syndrome; Vogt-Koyanagi-Harada; like Syndrome